(untitled) (Música Hodie, 2025)
The study aims to reveal the influence of religious faith on musical compositions, in particular, to analyse the structure, symbolism and use of biblical texts in Baroque sacred music. Both musical and theological contexts of the works were used to reveal their significance for the contemporary listener. The role of Protestant and Catholic traditions as sacredmusic genres, such as masses, motets, cantatas, passions and oratorios, was emphasised. The structure of musical compositions, symbolism, and connection with liturgical texts and religious practice were analysed in detail. For instance, in Bach’s work, his religious convictions and his Lutheran faith were reflected in complex polyphonic compositions, where the use of biblical texts and Protestant chorales became a means of spiritual education and musical service. The works of his contemporaries, such as Georg Friedrich Handel and Dietrich Buxtehude, who, similarly to Bach, used religious texts and symbolism to create deep spiritual works that affected listeners on an emotional and theological level, are also explored. In his oratorios, including Messiah, Händel-Werke-Verzeichnis 56 and Israel in Egypt, Handel skilfully combined dramatic musical forms with biblical stories to create epic works that emphasise the greatness of God. The study also explored the influence of Baroque sacred music on subsequent eras, on classical and romantic music. The results of the study demonstrate that Baroque sacred music has a profound impact on musical culture to this day, retaining its relevance and influence on religious perception.